Exosomal Transfer of miR-185 Is Controlled by hnRNPA2B1 and Impairs Re-endothelialization After Vascular Injury - Si, Yi; Liu, Fei; Wang, Dongqing; Fang, Chao; Tang, Xiao; Guo, Baolei; Shi, Zhenyu; Dong, Zhihui; Guo, Daqiao; Yue, Jianing; Fu, Weiguo (Frontiers in Cell and Developmental Biology, 2021)
Dysfunction of endothelial cells (ECs) contributes to restenosis after vascular reconstruction for patients with coronary artery disease (CAD). The intercellular communication between ECs and vascular smooth muscle cells (VSMCs) might be critical in the development of restenosis and can be mediated by exosomes carrying functional microRNAs. miR-185 is reported to be associated with atherosclerosis, whether it plays a similar role in restenosis is unknown. In this study, we observed an elevated level of extracellular miR-185 in platelet-derived growth factor (PDGF)-stimulated VSMCs. The medium from PDGF-stimulated VSMCs promoted miR-185 expression in rat aortic ECs and inhibited EC angiogenesis. PDGF-stimulated VSMCs transferred miR-185 into ECs via exosomes. Furthermore, we found that the CXCL12 gene, a target of miR-185, is essential for the angiogenic potential of ECs. Exosomes derived from miR-185 mimic transfected VSMCs attenuated re-endothelialization after vascular injury. Moreover, we show that exosome-mediated miR-185 transfer is modulated by hnRNPA2B1. We also observed that hnRNPA2B1 is up-regulated during neointima formation and hnRNPA2B1 inhibition accelerates re-endothelialization and attenuates neointima formation following carotid injury. Taken together, our results indicate that exosomal miR-185 transfer from VSMCs to ECs is controlled by hnRNPA2B1 and impairs re-endothelialization after vascular injury.